2013
DOI: 10.1084/jem.20122300
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells are trigger and target of the glucocorticoid response that prevents lethal immunopathology in toxoplasma infection

Abstract: CD4+ T cells regulate their own activity during toxoplasma infection by driving a glucocorticoid response, which results in feedback inhibition of Th1 cytokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…We believe that this true ex vivo analysis reveals the tightly regulated dynamics of T cell activation that occurs in vivo . This concept is supported by a recent report in which the role of glucocorticoids in the regulation of T cell responses was only evident when experiments were performed in the way we report here; T cells were hyperactive if analyzed after the traditional in vitro restimulation [34]. …”
Section: Discussionsupporting
confidence: 83%
“…We believe that this true ex vivo analysis reveals the tightly regulated dynamics of T cell activation that occurs in vivo . This concept is supported by a recent report in which the role of glucocorticoids in the regulation of T cell responses was only evident when experiments were performed in the way we report here; T cells were hyperactive if analyzed after the traditional in vitro restimulation [34]. …”
Section: Discussionsupporting
confidence: 83%
“…WT mice survived this challenge, yet mice lacking T-bet succumbed to infection between days 9 and 14 post-infection (Figure 3a). In many instances, susceptibility to T. gondii is either a consequence of an inability to control parasite replication (21, 38, 39) or the development of T cell-mediated immune pathology (40–43). In order to determine the cause of the increased mortality seen in T-bet −/− mice, parasite burden and levels of immune-mediated damage were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…gondii (Kugler et al, 2013), only limited recovery in thymocyte numbers in WT mice was observed during the chronic phase of infection ( Fig. 6 A), although overall thymocyte composition appeared to normalize ( Fig.…”
Section: Persistent Loss Of Thymic Function During Chronic T Gondii mentioning
confidence: 97%
“…We have previously shown that GCs are induced during acute T. gondii infection (Kugler et al, 2013), and this type of stress response is known to lead to thymic atrophy caused by loss of CD4 + CD8 + (double-positive; DP) thymocytes. Nevertheless, in T. gondii-infected mice, the loss in thymocytes was more general and not restricted to this DP population ( Fig.…”
Section: T Gondii Infection Induces a Persistent Thymic Atrophy Thatmentioning
confidence: 99%